Anger and Posttraumatic Stress Disorder Symptom Severity in a Trauma‐Exposed Military Population: Differences by Trauma Context and Gender. Issue 6 (18th November 2015) - Worthen, Miranda; Rathod, Sujit D.; Cohen, Gregory; Sampson, Laura; Ursano, Robert; Gifford, Robert; Fullerton, Carol; Galea, Sandro; Ahern, Jennifer
Abstract: Studies have found a stronger association between anger and posttraumatic stress disorder (PTSD) severity in military populations than in nonmilitary populations. Two hypotheses have been proposed to explain this difference: Military populations are more prone to anger than nonmilitary populations, and traumas experienced on deployment create more anger than nondeployment traumas. To examine these hypotheses, we evaluated the association between anger and PTSD severity among never‐deployed military service members with nondeployment traumas ( n = 226) and deployed service members with deployment traumas ( n = 594) using linear regression. We further examined these associations stratified by gender. Bivariate associations between anger and PTSD severity were similar for nondeployment and deployment events; however, gender modified this association. For men, the association for deployment events was stronger than for nondeployment events (β = .18, r = .53 vs. β = .16, r = .37, respectively), whereas the reverse was true for women (deployment: β = .20, r = .42 vs. nondeployment: β = .25, r = .65). Among men, findings supported the hypothesis that deployment traumas produce stronger associations between PTSD and anger and are inconsistent with hypothesized population differences. In women, however, there was not a clear fit with either hypothesis.